P41 Genetic variation in biliary transporters as a susceptibility factor for cholangiocarcinoma. (16th November 2010) - Wadsworth, C; Dixon, P; Wong, J; Chapman, M; McKay, S; Sharif, A; Spalding, D; Pereira, S; Thomas, H; Taylor-Robinson, S; Whittaker, J; Williamson, C; et al.
Abstract : Introduction: Cholangiocarcinoma (CC) is increasing in incidence globally but its pathogenesis remains poorly understood. Chronic inflammation of the bile duct and cholestasis are major risk factors but most cases in the West are sporadic. Genetic polymorphisms in biliary transporter proteins have been implicated in benign biliary disease and, in the case of progressive familial cholestasis, have been associated with childhood onset of CC. A recent case-control study of a single nucleotide polymorphism c.3972C>T (rs3740066) in ABCC2, reported an association with CC. Aim: To investigate five biologically plausible candidate genes as susceptibility factors for cholangiocarcinoma; ABCB11 (BSEP); ABCB4 (MDR3); ABCC2 (MRP2); ATP8B1 (FIC1) and NR1H4 (FXR). Method: Germline DNA was collected from 172 Caucasian individuals with confirmed CC. A control cohort of 256 healthy Caucasian patients was included in the analysis. 73 SNPs were selected using the HapMap database in Haploview 4.1 (build 22; MAF >0.05, pair-wise comparisons only) to capture the majority of common genetic variation around the five candidate loci. Genotyping was undertaken with a competitive allele-specific PCR based robotic genotyping system. Confirmation of Hardy-Weinberg equilibrium and Cochran-Armitage trend testing were performed using PLINK v1.07. Haplotype frequencies were compared using haplo.stats v1.4.4. Results: All 73 SNPs were in Hardy-Weinberg Equilibrium. Four SNPs in ABCB11 were associated with altered susceptibility to CC, including the V444A polymorphism (c.1331T>C, rs2287622, p<0.007) but these associations did not retain statistical significance after Bonferroni correction for multiple testing. Haplotype analysis of the genotyped SNPs in ATP8B1 identified significant differences in frequencies between cases and controls (global p value 0.005). None of the SNPs in ABCC2, including rs3 740 066, showed association with CC. Haplotype analysis in ABCC2 failed to detect significant association. Conclusion: This is the largest study to date of biliary transporter polymorphisms as susceptibility factors for CC. The previously reported association between SNP rs3 740 066 in ABCC2 and CC was not replicated. Haplotypes in ATP8B1 demonstrated a significant difference between CC and control groups. There was also a trend towards significant association of V444A with CC. V444A has been strongly implicated in other cholestatic diseases. Given the biological plausibility of polymorphisms in ABCB11 and ATP8B1 as risk modifiers for CC, further study in a validation cohort is required.